2020
DOI: 10.1038/s41598-020-60139-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics of Populus euphratica forests in different stages in the upper reaches of the Tarim River in China

Abstract: We selected four Populus euphratica Oliv. forest plots (100 m × 100 m) in the upper reaches of the Tarim River in the Xinjiang Uygur Autonomous Region of China. Each of the four forest plots was chosen to represent a different growth and death stage of P. euphratica forest: juvenile forest, mature forest, dying forest, and dead forest. In each plot, we measured the coordinates, DBH, height, and status of all P. euphratica individuals. We used (1) spatial pattern analysis to explore spatial distribution pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…This was also true for the ANN, DMI, and I δ indexes ( Table 3 ). These observations agree with previous work findings reported by Zhang et al (2019) and Miao et al (2020) , which showed that in the upper reaches of the Tarim River, the P. euphratica live trees were typically randomly distributed. The trees in the middle reaches were unevenly distributed, except for two plots (M1 and M2) closest to the river ( Figure 5 ), with the g( r ) function producing high values above the CSR null model confidence interval.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This was also true for the ANN, DMI, and I δ indexes ( Table 3 ). These observations agree with previous work findings reported by Zhang et al (2019) and Miao et al (2020) , which showed that in the upper reaches of the Tarim River, the P. euphratica live trees were typically randomly distributed. The trees in the middle reaches were unevenly distributed, except for two plots (M1 and M2) closest to the river ( Figure 5 ), with the g( r ) function producing high values above the CSR null model confidence interval.…”
Section: Discussionsupporting
confidence: 93%
“…Various traditional field measurement methods have been used for analyzing the spatial distribution pattern of riparian forests ( Han et al, 2014 ; Xu et al, 2016 ; Miao et al, 2020 ). However, traditional methods are hard to obtain detailed structural parameters, and spatial distribution patterns of the forest stand in the same period, which hindering our deeper understanding of forest structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some researchers indicated that P. euphratica population regeneration in the lower reaches of Tarim River showed a decline type, the proportion of young plants in the population decreased significantly or even lacked, population was mostly over mature forest plants and the overall performance of the decline trend ( Zhou et al, 2018 ). Currently, most studies of P. euphratica were focus on heteromorphic leaves ( Li et al, 2020a ; Li et al, 2020b ), photosynthetic physiological characteristics ( Wang et al, 2014 ), water use efficiency ( Zhou et al, 2019 ), population structure ( Miao et al, 2020 ), etc , while few studies on the relationship between plant and rhizosphere soil fungal community composition and diversity. Therefore, the goal of our work was to (1) analyze the composition and diversity of rhizosphere soil fungi of P. euphratica at different growth stages in the lower reaches of the Tarim River; (2) explore the dominant fungi in the P. euphratica rhizosphere at different stages, and the change of rhizosphere soil physical and chemical properties; (3) elucidate the correlation between fungal community composition and environmental factors.…”
Section: Introductionmentioning
confidence: 99%